INFLUENCE OF APOE GENOTYPES ON BIOCHEMICAL INDICES OF IRON AND LIPID METABOLISM IN PATIENTS WITH THE ENDOMETRIUM NEOPLASTIC DISEASES AND HEAL THY WOMEN - T. A. Ivanova; M. V. Poluektova; V. A. Khorokhorina; O. A. Vorob’eva; T. V. Chirkova; L. S. Mkrtchyan; N. I. Sychenkova; L. I. Krikunova; N. I. Ryabchenko (Исследования и практика в медицине)
Objective. APOE genotype association with the level of iron in plasma and the risk of endometrial neoplastic diseases has not been studied. The aim of the work was to analyze the genotypic associations of the apolipoprotein E (APOE) with iron and lipid levels in endometrial hyperplasia (EH)/endometrial cancer (EC) patients and healthy women.Materials and methods. The biochemical blood levels of iron and cholesterol metabolism detected in women d with diagnosed endometrial hyperplasia (53), endometrial cancer (87) and healthy women (70) are determined on an automated analyzer «OLYMPUS AU – 400”. The genotyping was performed with a PCR-RFLP (polymerase chain reaction with restriction fragment length polymorphism) technique.Results. A statistically significant decrease in the levels of serum iron, transferrin saturation, high-density lipoprotein on the one hand, and a statistically significant increase in body mass index, triglycerides, very low density lipoproteins, atherogenic index in patients with endometrial adenocarcinoma was observed. Statistically significant differences in the distribution of E3, E4, E2 allele frequencies between patients and healthy women (P = 0.048) was revealed. E3 allele frequency was reduced, and the E2 allelewas increased in patients with EC. It was shown that the serum iron level was significantly increased in EC patients and healthy carriers of the genotype E3/E2 (P= 0,0014 and 0,0363 respectively). There was significantly elevated triglyceride level in carriers of the minor genotypes E2/E4, E4/E4 among patients with EH (0,0389).Conclusions. Genotype E3/E2 compared with other APOE genotypes under study is associated with elevated levels of iron and the risk of endometrial cancer. The association APOE 2/2, 2/4, 4/4 as well as 3/2 with endometrial neoplastic diseases requires further investigation. The data obtained can be the basis for the creation of a marker system for determining a high level susceptibility to malignant disease of the female reproductive system.